Keluarga Gagal Di Era Digitalisasi Ditinjau Dalam Perspektif Hukum Islam - Kamalin, Muhammad (Journal of Legal Sustainability, 2024)
The purpose of this research is to find out the causes of family failure and to find out the Islamic law review of the causes of family failure. The method used in this research is analytical descriptive research which aims to find out family problems to find out the Islamic law review of the problems of failed families in the era of digitalization. The research results provide an illustration that the current problem of failed families is due to the loss of family function or family dysfunction. As a result, family members are not fully controlled by their parents, juvenile delinquency occurs, teenagers spend more time outside the home than at home, even though children are the relay for future leaders. Likewise, the consequences of family poverty; In the end, there are husbands/wives who work abroad to earn a living as workers, hoping to make family life prosperous, but the integrity of the family is not perfect. This is a picture of a failed family in the digital era that lacks understanding of religious teachings or Islamic law as standards in family life.